Development and evaluation of a Novel Real-Time PCR assay for specific detection of chlamydia psittaci in clinical respiratory samples - Mohd Zin, Nur Bainun; Mohmd Azman, Siti Norsuhaida; Ahmad, Noorlis; Mohamed Zahidi, Jama’ayah; Zamri, Hana Farizah; Hashim, Rohaidah; Mohammad Ridhuan Mohd Ali, Mohammad Ridhuan; Zainal-Abidin, Nurhamimah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Chlamydia psittaci is an obligate intracellular Gram-negative bacterium that is zoonotic causing diseases called psittacosis in humans. Humans are usually infected through inhalation, which often leads to atypical pneumonia, with fatal outcome if left untreated. Early and accurate diagnosis is crucial for effective clinical management and containment of potential outbreaks. Nevertheless, C. psittaci infections are often underestimated as their clinical and laboratory presentations closely resemble those of other respiratory infections. Traditional diagnostic methods relied on serology and culture but has limitations in specificity, sensitivity and biosafety. This study aimed to develop and evaluate a rapid, specific and sensitive real-time PCR assay targeting the ompA gene for detection of C. psittaci in human respiratory samples. A synthetic plasmid containing an ompA gene fragment was used as a positive control, eliminating the need for hazardous live cultures while ensuring assay stability. Specificity testing against 28 bacterial strains revealed no cross-reactivity, and in silico PCR analysis against 268 bacterial genomes confirmed exclusive amplification of C. psittaci. Spiking experiments with human respiratory samples (n=43) demonstrated robust detection across various matrices and concentrations, with no amplification in non-spiked controls, confirming absence of false positives. The assay achieved a detection limit of 0.0002 pg (~25 DNA copies) with 97.84% amplification efficiency and an R² of 0.9995, indicating high precision and reproducibility. These findings establish the developed real-time PCR assay as a highly specific and sensitive diagnostic tool for C. psittaci, enabling rapid and accurate detection to support timely clinical management and outbreak control.